2021
DOI: 10.21203/rs.3.rs-143729/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex differences in association between cognitive impairment and clinical correlates in Chinese patients with first-episode drug-naïve schizophrenia

Abstract: Background Schizophrenia is a complex mental illness with significant sex differences. Cognitive impairment is common in patients with schizophrenia, even in remission. This study was designed to examine the sex differences in the relationship between cognitive impairment and clinical correlations with first-episode drug-naïve (FEDN) schizophrenia. Methods 93 FEDN patients (male/female = 45/48) and 160 controls (male/female = 74/86) were enrolled to compare the sex differences in cognitive functions measure … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Zhang et al found that male SCZ patients showed worse cognition than females in social cognition, processing speed, working memory, verbal learning and visual learning [ 25 ]. Other researchers had similar findings [ 26 – 28 ]. Moreover, sex differences in oxidative stress have been reported in numerous basic and clinical studies, wherein male SCZ patients exhibit higher oxidative stress than female SCZ patients [ 29 , 30 ].…”
Section: Introductionsupporting
confidence: 77%
“…Zhang et al found that male SCZ patients showed worse cognition than females in social cognition, processing speed, working memory, verbal learning and visual learning [ 25 ]. Other researchers had similar findings [ 26 – 28 ]. Moreover, sex differences in oxidative stress have been reported in numerous basic and clinical studies, wherein male SCZ patients exhibit higher oxidative stress than female SCZ patients [ 29 , 30 ].…”
Section: Introductionsupporting
confidence: 77%
“…The review by Mendrek and Mancini-Marïe (8) highlighted that several studies found better neurocognitive functions in female than in male patients, while others found an opposite pattern or no gender difference. Findings of more recent studies did not clarify this picture, as a greater neurocognitive impairment has been reported in males (15,71,(80)(81)(82) but also in females (83), or no gender differences (67). Moreover, when gender differences were found, the patterns of impaired cognitive domains in males and females varied among studies.…”
Section: Impairment In Neurocognition and Social Cognitionmentioning
confidence: 88%
“…Discrepancies in these findings may be due to the heterogeneity of clinical expression in schizophrenia (8), such as the presence/absence of severe negative symptoms in the clinical picture, as they have been found correlated to cognitive impairment in several studies (79,87). Also methodological factors such as differences in sample size or the heterogeneity of tests used to assess cognitive functions may account for discrepancies among studies; as a matter of fact, among the above reported studies, only three (80,82,83) assessed neurocognitive domains by means of the MATRICS Consensus Cognitive Battery, which is considered the gold standard to reliably assess neurocognitive functions in subjects with schizophrenia (88).…”
Section: Impairment In Neurocognition and Social Cognitionmentioning
confidence: 99%